Regulation of Compound Leaf Development by PHANTASTICA in Medicago truncatula . Issue 1 (11th November 2013) - Ge, Liangfa; Peng, Jianling; Berbel, Ana; Madueño, Francisco; Chen, Rujin
Abstract : A MYB domain protein maintains petiole identity by repressing expression of a motor organ identity gene and promoting petiole and stipule development in Medicago truncatula . Abstract: Plant leaves, simple or compound, initiate as peg-like structures from the peripheral zone of the shoot apical meristem, which requires class I KNOTTED-LIKE HOMEOBOXI (KNOXI) transcription factors to maintain its activity. The MYB domain protein encoded by the ASYMMETRIC LEAVES1/ROUGH SHEATH2/PHANTASTICA ( ARP ) gene, together with other factors, excludes KNOXI gene expression from incipient leaf primordia to initiate leaves and specify leaf adaxial identity. However, the regulatory relationship between ARP and KNOXI is more complex in compound-leafed species. Here, we investigated the role of ARP and KNOXI genes in compound leaf development in Medicago truncatula . We show that the M. truncatula phantastica mutant exhibited severe compound leaf defects, including curling and deep serration of leaf margins, shortened petioles, increased rachises, petioles acquiring motor organ characteristics, and ectopic development of petiolules. On the other hand, the M. truncatula brevipedicellus mutant did not exhibit visible compound leaf defects. Our analyses show that the altered petiole development requires ectopic expression of ELONGATED PETIOLULE1, which encodes a lateral organ boundary domain protein, and that the distal margin serration requires the auxin efflux protein M. truncatula PIN-FORMED10 in the M. truncatula phantastica mutant.